1999
DOI: 10.2754/avb199968010041
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Slope of the Plasma Lactate Accumulation Curve and Working Capacity in Andalusian Horses

Abstract: The main objective of this study was to analyse the relationship between the slope of the plasma lactate accumulation in response to exercise and working capacity in two groups of Andalusian horses of different age.The horses were subjected to increasing intensity tests, comprising both submaximal and maximal velocities. Heart rate was monitored throughout the exercise and jugular venous blood samples were withdrawn at rest, after each workload and during the first 30 min. of recuperation. Working capacity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…These observations were also described by Muñoz et al (1999), who found lower HR response to the exercise in trained and adapted horses to the exercise in relation to untrained animals.…”
Section: Resultssupporting
confidence: 71%
“…These observations were also described by Muñoz et al (1999), who found lower HR response to the exercise in trained and adapted horses to the exercise in relation to untrained animals.…”
Section: Resultssupporting
confidence: 71%
“…Field exercise tests, however, have an advantage over laboratory tests, in that the athlete is tested whilst performing the activity for which they have trained under conditions more reflective of competition (MacDougall and Wenger 1991). Field tests have also been used to describe the relationship between heart rate, blood lactate concentrations and speed (Anderson 1975;Bayly et al 1987;Evans et al 1993;Harkins et al 1993;Von Wittke et al 1994;Guhl et al 1996;Davie and Evans 2000) and the effects of training (Anderson 1975;Wilson et al 1983;Linder et al 1992;Valette et al 1996) in Thoroughbred horses and Andalusian horses (Munoz et al 1999). The difficulty with field tests, however, is in the control over the different variables during the testing conditions.…”
Section: Introductionmentioning
confidence: 99%